Flickskolan i Luleå : En studie om verksamheten och undervisningen under 1885-1945 ur ett genusperspektiv - Hammer, Nina (2016)
The purpose of this study was to investigate and analyze how the girls' school in Luleå 1885-1945 from a gender perspective with a focus on function and education over time. Timetables have been analyzed from a quantitative method. Subject contents on the other hand have been objected by a qualitative method because interpreted and close reading has been the key tool for the analysis. Due to the information regarding the number of teaching lessons and subject contents, conclusions have been drawn with the help of the interpretations made based on the source material. It has been possible to reveal a breakpoint for teaching in the normal school competence. Because of the normal school competence was French’s strong position in the girls' school lost. The analysis show that gender was constructed in the girls' school in Luleå, but it does not explicitly was the school's mission. The content of education reflects that girls were socialized to be girls on the girls’ school. Validerat; 20160602 (global_studentproject_submitter)